2018
DOI: 10.1177/1947603518758436
|View full text |Cite
|
Sign up to set email alerts
|

Local Anesthetics’ Toxicity toward Human Cultured Chondrocytes: A Comparative Study between Lidocaine, Bupivacaine, and Ropivacaine

Abstract: Objective In orthopedic joint injection, the most frequently used local anesthetics are ropivacaine, bupivacaine, and 1% or 2% lidocaine. The aim of this study was to examine effects of these various anesthetics on the viability of human chondrocytes. Our hypothesis was that all local anesthetics tested damage human chondrocytes in vitro. Methods Primary human chondrocytes were isolated and cultured from 6 donated human knee joints (mean age of donors 61.2 years). Local anesthetics were added to these cultures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…Our results are in accordance with Durant et al that shows the protective effect of PRP against 1% and 0.5% LD bupivacaine on human chondrocytes [ 26 ]. Moreover, our results demonstrate that PRP is also able to protect chondrocytes at the concentration of 1.8% which is close to the maximum recommended in vivo dose (2%) [ 27 ], and shows that PRP may reduce LD-induced apoptosis. Baboldashti et al [ 25 ] previously demonstrated that PRP protects tenocytes from the adverse effects of dexamethasone and ciprofloxacin, and proposed using PRP to minimize the effect of unsafe therapeutic treatments.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our results are in accordance with Durant et al that shows the protective effect of PRP against 1% and 0.5% LD bupivacaine on human chondrocytes [ 26 ]. Moreover, our results demonstrate that PRP is also able to protect chondrocytes at the concentration of 1.8% which is close to the maximum recommended in vivo dose (2%) [ 27 ], and shows that PRP may reduce LD-induced apoptosis. Baboldashti et al [ 25 ] previously demonstrated that PRP protects tenocytes from the adverse effects of dexamethasone and ciprofloxacin, and proposed using PRP to minimize the effect of unsafe therapeutic treatments.…”
Section: Discussionsupporting
confidence: 72%
“…Dilutions of LD and PRP were prepared in DPBS. Although the most commonly administered doses of LD are 1% and 2% [ 27 ] we used 1.8% instead 2% in order to obtain 10% of PRP in association with LD, as the highest commercially available concentration of LD is at 2%.…”
Section: Methodsmentioning
confidence: 99%
“…Local anesthetics such as bupivacaine and ropivacaine were used for peripheral nerve block, sympathetic nerve block, local in ltration, epidural and caudal blocks [11,[26][27][28]. Combination dexmedetomidine with bupivacaine or ropivacaine can prolong the analgesic effect [14,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…24 Ropivacaine 0.1 to 0.2% is considered the safest local anesthetic to use regarding chondral toxicity, but low-dose bupivacaine (0.0625%) is also acceptable and several times less expensive than ropivacaine. 24,25 Nevertheless, it would still seem reasonable to inject a local anesthetic agent into end-stage osteoarthritic joints with little or no remaining cartilage for symptomatic relief before joint replacement or to relieve some of the discomfort that may accompany steroid injection (steroid flare).…”
Section: Tip 10: Injectablesmentioning
confidence: 99%